ANALISIS PRODUKTIVITAS DAN PENGHEMATAN AKIBAT KLASTERISASI SEKTOR AGROINDUSTRI DI PROVINSI LAMPUNG - Affandi, M. Irfan (Lampung University)
The research objectives are to analyze productivity of clusteritation economies in the agroindustrial sectors. The data analysis use survey result of medium and large industrial (1998-2005) and applying indexs to determine an clusteritationâs power. Cobb-Douglas production function was used to measure the clusteritation economies.Â The existing of the localization and urbanization in the agroindustrial sectors were significantly proved.